An Early Holocene Primary Dolomite Layer of Abiotic Origin in Lake Sayram, Central Asia. Issue 23 (7th December 2021) - Cheng, Jianru; Meng, Xianqiang; Zhang, Enlou; Jiang, Qingfeng; Ni, Zhenyu; Ji, Junfeng
Abstract: The "dolomite problem" is a long‐standing puzzle in sedimentology and mineralogy. Previous studies have shown that some dolostones are formed by microbes or in hydrothermal–burial environments. Here, we provide a different case in which an abiotic and Ca‐rich dolomite layer precipitated in Lake Sayram, Central Asia, during the early Holocene. The 12‐cm‐thick layer consists of abundant partially ordered dolomite crystals (mean > 50 wt% and maximum = 81 wt%) which have euhedral and rhombohedral shapes and weak cation ordering. Transmission electron microscopy reveals that even in a single crystal, compositions vary among different domains. Mineralogical and isotopic evidence suggests that these dolomites are of primary and abiotic origin. We infer that this dolomite layer might be the product of day and night temperature cycling of shallow lake water under local warming trend. This study provides evidence for abiotic dolomites forming at ambient temperature. Plain Language Summary: Dolostone is common in ancient rocks but rare in modern marine sediments, and dolomite is notoriously difficult to synthesize without microbes at room temperature; this is known as the "dolomite problem". In many studies, microbes have often been associated with dolomite, and synthesis by microbial mediation has succeeded. However, the mineralogy of microbial dolomites has been questioned and not all massive dolostones have been found with microbial structures. Hydrothermal–burial alteration is another promising solution, but recent studies have demonstrated that dolostones could also form at surface temperatures (<60°C). In this study, we investigated a Holocene lacustrine dolomite layer (12‐cm‐thick) precipitated without microbes or burial alteration. Our results demonstrated that these dolomites have obvious cation ordering and euhedral crystals, and their oxygen isotope values are similar to ostracods in the same horizon, suggesting a primary origin. These euhedral and rhombic dolomite grains are consistent with dolomite precipitated slowly in an abiotic way rather than by microbial mediation. We infer the dolomite layer might be an aftermath of the day and night temperature cycling of shallow lake water resulting from local warming and aridification. This study provides evidence that partially ordered dolomite, as an intermediate phase of ideal dolomite, can precipitate abundantly in ambient environments. Key Points: A 12‐cm‐thick early Holocene lacustrine layer consists of partially ordered dolomites with a mean >50 wt% and a maximum of 81 wt% Euhedral and rhombic crystals and similar C–O isotopes to ostracods suggest that these dolomites are primary and abiotic Diel temperature cycling helps Mg ion incorporation, leading to internal heterogeneity of composition and obvious cation ordering